Positionality at the Center: Constructing an Epistemological and Methodological Approach for a Western Feminist Doctoral Candidate Conducting Research in the Postcolonial. Issue 4 (25th November 2015) - Vanner, Catherine
As a Western feminist supporting and researching gender equality in education in postcolonial contexts, I often wonder: Am I doing more harm than good? The privilege of my social location means that my efforts to support education in postcolonial contexts risk being patronizing, insulting, threatening, imperialist, and recolonizing. Yet neglecting and ignoring postcolonial contexts similarly reflects and reproduces a privileged position. I provide a tentative framework designed to address positionality, power, and privilege while creating an ethical research process for working in a postcolonial context. Beginning with an identification of positionality, the objectives of research, and guiding theoretical frameworks to situate the research in relation to the participants and context, I proceed to establish a methodology designed to minimize the negative effects of power and maximize participants' empowerment. I position myself as a bricoleur, layering feminist standpoint theory and postcolonial theory, and propose the collaborative data collection and analysis techniques, with particular attention to ethical and cultural sensitivity, using a social constructivist approach to grounded theory. This article highlights the need for Western researchers to reflect upon the power dynamics of their research in postcolonial contexts and develop a strategy for conducting empowering research that prevents the misrepresentation and exploitation of participants. Observations from my doctoral thesis data collection provide examples of how these concepts were operationalized in practice as well as reflections on the disconnect between theorizing and conducting ethical research in postcolonial contexts.